Habits of donning headscarf: correlation between neck range of motion and proprioception among female students of IIUM Kuantan campus, Malaysia - Mohd Dar, Shahid; Mohd Faudzy, Nur Syuhada (Malaysian Public Health Physicians' Association, 2024)
Investigating the potential relationship between cervical spine mobility and proprioception among collegiate student with hijab wearing habits is an interesting avenue of research, particularly given the cultural significance of the hijab and its potential impact on daily activities and posture. The present study aimed to quantify the cervical spine mobility and assess for proprioceptive deficits among hijab wearing women. A total of 122 subjects between the age group of 20-26 years were selected from International Islamic university Kuantan. Cervical spine mobility and proprioception were assessed using universal goniometer and Joint position error method (JPE) respectively. Results were described in means, standard deviations, frequencies, and percentages. The mean and standard deviation (M ± S.D) of cervical flexion, cervical extension, right lateral flexion, left lateral flexion, right rotation, and left rotation ranges from 50.0 ± 9.87, 52.7 ± 8.09, 34.3 ± 6.63, 3.43 ± 6.63, 68.9 ± 6.15, 67.8 ± 6.23 degrees respectively. On the other hand, the (M ± S.D) of JPE for cervical flexion, cervical extension, right lateral flexion, left lateral flexion, right rotation, and left rotation were 1.00 ± 0.16, 1.00± 0.09, 1.00 ± 0.18, 1.00 ± 0.09, 1.00 ± 0.28, and 1.00 ± 1.00 degrees respectively. Pearson’s Correlation revealed a negligible linear relationship between cervical mobility and JPE for all cervical movements except for right lateral flexion (r = +0.239 p = 0.008), where a weak positive relationship was observed. These findings suggest that though the cervical mobility may get affected due to wearing of hijab in long term, but it does not seem to affect the cervical proprioception significantly.